2015
DOI: 10.1007/s00198-015-3156-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone structure assessed by HR-pQCT, TBS and DXL in adult patients with different types of osteogenesis imperfecta

Abstract: Trabecular BMD and trabecular bone microstructure in particular are severely altered in patients with clinical OI-I and OI-III-IV. Low TBS and DXL and their significant associations to HR-pQCT parameters of trabecular bone support this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 39 publications
7
42
2
1
Order By: Relevance
“…For example, several groups have compared adults with osteogenesis imperfecta (OI) to apparently healthy subjects and showed severe trabecular deficits in radial and tibial parameters, especially in Tb.vBMD (−21% to −38.5%), Tb.N (−21.4% to −49.4%), and Tb.Sp. (+54.5% to +77.8%) . Although alterations were more severe in moderate–severe OI (type III/IV) than in mild OI (type I), the trabecular deterioration in all types of OI exceeded that observed in fracture subjects in the current study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…For example, several groups have compared adults with osteogenesis imperfecta (OI) to apparently healthy subjects and showed severe trabecular deficits in radial and tibial parameters, especially in Tb.vBMD (−21% to −38.5%), Tb.N (−21.4% to −49.4%), and Tb.Sp. (+54.5% to +77.8%) . Although alterations were more severe in moderate–severe OI (type III/IV) than in mild OI (type I), the trabecular deterioration in all types of OI exceeded that observed in fracture subjects in the current study.…”
Section: Discussioncontrasting
confidence: 61%
“…(+54.5% to +77.8%). (64)(65)(66) Although alterations were more severe in moderate-severe OI (type III/IV) than in mild OI (type I), (65) the trabecular deterioration in all types of OI exceeded that observed in fracture subjects in the current study. Recently, Rolvien and colleagues used HR-pQCT to compare bone microarchitecture in adults with OI and sex-and agematched subjects with early-onset osteoporosis (EOOP; a condition distinct from postmenopausal osteoporosis in that it is characterized by low bone mass and the occurrence of fragility fractures before the age of 50 years) and healthy subjects.…”
Section: Hr-pqct and Bone Diseasescontrasting
confidence: 61%
“…Altered bone microstructure and bone geometry, evaluated by HR‐pQCT, has been reported in patients with OI types I, III, and IV 28, 29. However, in two mosaic carriers, normal skeletal growth, bone density, and bone histology were found in spite of 40–75% burden of osteoblasts heterozygous for a COL1A1 mutation 30, which is concordant with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, in addition to significant relationships between TBS and trabecular microarchitecture, TBS was also related to cortical parameters and whole bone rather than trabecular stiffness. In contrast, in a cohort of patients with osteogenesis imperfecta, Kocijan et al (27) reported that TBS was related to trabecular but not cortical parameters. In our cross-sectional analyses, we found that, in patients with kidney disease before transplantation, TBS was related to trabecular microarchitecture and wholebone stiffness and failure load.…”
Section: Discussionmentioning
confidence: 88%